Building a Mammalian Retina: An Eye on Chromatin Structure - Daghsni, Marwa; Aldiri, Issam (Frontiers in Genetics, 2021)
Regulation of gene expression by chromatin structure has been under intensive investigation, establishing nuclear organization and genome architecture as a potent and effective means of regulating developmental processes. The substantial growth in our knowledge of the molecular mechanisms underlying retinogenesis has been powered by several genome-wide based tools that mapped chromatin organization at multiple cellular and biochemical levels. Studies profiling the retinal epigenome and transcriptome have allowed the systematic annotation of putative cis-regulatory elements associated with transcriptional programs that drive retinal neural differentiation, laying the groundwork to understand spatiotemporal retinal gene regulation at a mechanistic level. In this review, we outline recent advances in our understanding of the chromatin architecture in the mammalian retina during development and disease. We focus on the emerging roles of non-coding regulatory elements in controlling retinal cell-type specific transcriptional programs, and discuss potential implications in untangling the etiology of eye-related disorders.